Matriz de impactos intersetoriais em economia da defesa do Brasil - Ternus, Cássia Heloisa (2017)
Firstly, the present study aims the creation by a tool capable measuring and evaluating the intersectorial impacts on defense economics in Brazil. Defense studies economics have gained notoriety in the post-Cold Wartime; however, there is still no tradition in such research. Thus, there is an area for new studies, since in addition to being few; there are no consensus on the results. In Brazil, defense investments are low, concentrated in personnel payments and, regionally, in the Federal District and in the Southeast region. Moreover, the operation at research was on the construction of an Input-Output Matrix (IOM) with the inclusion of the National Defense sector, using the IOM in 2010 with updated values for 2015. The results indicate that the sector is not very significant defense in the national economy; nevertheless, they are very close to other public sectors. With regard to the Type II employment multiplier, defense occupies the 1st place, possibly due to the high salaries of the sector. Finally, as for the simulations, for Type II multipliers, a R$ 10 million shock would generate 191 jobs, R$ 12 million in added value and R$ 24.32 million in gross production.